Romania : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper examines Romania's external stability risks. Recent Romanian data indicate high increases in real wages, not matched by comparable productivity gains. Both the government and the National Bank of Romania (NBR) have highlighted the importance of a responsible and stabilizing wage policy for macroeconomic stability in the country current juncture. A three-pronged approach is recommended that encompasses capacity building and improved transparency, a medium-term framework for fiscal policy, and increased use of independent fiscal expertise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet